A Growth Chart for Premature and Other Infants - Gairdner, Douglas (1971)
The growth chart covers the period from 28 weeks of fetal life to age 2 years, and allows weight, length, and head circumference to be charted. The time scale is logarithmic, providing the convenience of an extended scale for the earlier months of life, and giving the graphs an approximately linear form. Separate charts for boys and girls are provided, with 10th, 50th, and 90th centiles. Weight charts of individual low birthweight infants illustrate the striking `catch-up' growth often achieved by these infants.